Context and coherence : the logic and grammar of prominence / Una Stojnić. - Stojnić, Una (Oxford University Press, 2021)
Natural languages are riddled with context-sensitivity. One and the same string of words can express many different meanings on occasion of use, and yet we understand one another effortlessly, on the fly. How do we do so? What fixes the meaning of context-sensitive expressions, and how are we able to recover the meaning so effortlessly? This book offers a novel response: we can do so because we draw on a broad array of subtle linguistic conventions that determine the interpretation of context-sensitive items.